GAMBARAN DUKUNGAN KELUARGA DAN HARGA DIRI ANAK TUNADAKSA DI SLB N BANTUL BAGIAN D YOGYAKARTA (Studi Kualitatif) - Yanita Trisetiyaningsih (Fakultas Ilmu Kesehatan, 2015)
Background : Self esteem very have an effect on to someone attitude in looking at herself and ability to bring ourself in life. Self esteem owned by everybody is including children of Tunadaksa. Existence of handicap at theirself will influence child of Tunadaksa in looking at theirself and adaptation process of theirself. Forming of self esteem influenced by family support as environment which was first time recognized by child. Intention of this research is to know the image of family support and child self esteem of Tunadaksa in SLB N Bantul Yogyakarta.Method : This Research is research type qualitative with approach method is non device and eksperimental of cross sectional ( transversal crosscut) which have the character of descriptively of eksploratif. The sample has got 5 their’s parents and Tunadaksa 5 people. Way of data collecting is to pass circumstantial interview and attitude observation of child behaviour when residing in at home and school.Result : Of research getting that most old fellows have family support which do well by child of Tunadaksa when residing in at home, they always entangle and involve child in every family activity within doors. Most old fellows also have good family support in social environment, they always invite child to follow social activity and interaction with others. Most parents have good family support when in school, they give the attention of in the case of education of child, always fulfill requirement of child school. Some of children of Tunadaksa selfrespecting which are positive when residing in at home, they can and will follow every family activity. Most children of Tunadaksa selfrespecting which are positive when residing in social environment, they do not get trouble in have socialization and interaction with others. Most children of Tunadaksa selfrespecting which are positive when residing in school, they remain to can do the obligation of as and student have interaction with others in school.Conclusion : This research is getting that most of parents have family support which do well by child of Tunadaksa, the parent always pay attention requirement of child, entangling child in every family activity and most children of Tunadaksa selfrespecting which are positive, they don’t get trouble in have interaction and communicate with others, can run the role of good at home, in social environment and when in school. Keyword : Family support, Self esteem, Child of Tunadaksa